Knowledge as a mediator between HRM practices and innovative activity - Lopez‐Cabrales, Alvaro; Pérez‐Luño, Ana; Cabrera, Ramón Valle (Human Resource Management, 2009)
AbstractThe objective of this paper is to test how human resources management (HRM) practices and employees' knowledge influence the development of innovative capabilities and, by extension, a firm's performance. Results confirm that HRM practices are not directly associated with innovation unless they take into account employees' knowledge. Specifically, our analyses establish a mediating role for the uniqueness of knowledge between collaborative HRM practices and innovative activity, a positive influence of knowledge‐based HRM practices on valuable knowledge, and a positive contribution of innovations to the company's profit. We tested hypotheses in a sample of firms from the most innovative Spanish industries through structural equation modeling. © 2009 Wiley Periodicals, Inc.